PENERAPAN SISTEM REWARD DAN PUNISHMENT PEGAWAI DI BADAN KEPEGAWAIN PELATIHAN DAN PENDIDIKAN DAERAH KABUPATEN MAMASA - RAMBULANGI, ADE SUNARYA A.L; POSUMAH, JOHNNY HANNY; LONDA, VERY (Sam Ratulangi University, 2017)
Abstract : Reward and punishment aims to increase employee motivation, so that employees will be maximized in work.This research aims to find out, how the application of reward and punishment system in the employment agency trainingand education in district Mamasa. This research uses qualitative method that is research type which is used to research oncondition where natural object is key instrument, data collecting technique is done by triangulation (combination), dataanalysis is inductive and qualitative research result more emphasize meaning from generalization. Informants in thisresearch amounted to 10 people, namely head employment agency 1 person, secretary 1 person, head of field 3 people andoffice employees 5 people. The results of this research can be seen that the rewards and punishment applied in theemployment agency personnel training and education in district Mamasa in terms of rewards in the form of incentivematerial and non-material incentive; and punishment in the form of preventive and repressive. It can be said that has notbeen applied maximally by the head of the employment agency and based on existing research can be seen that there arestill many complaints from the employees to the leadership regarding the implementation of rewards and punishment. Lackof firmness, improper rewarding, unfair and uneven punishment are factors that cause employees to complain against theleadership. Refers to some of the results of this research then as a suggestion in solving the problem in this research thatshould be more appropriate in giving awards to employees who achievement of performance, more firm in givingpunishment, both before the occurrence of violations and after the occurrence of violations and be fair and equitable ingiving punishment.Keywords : Reward, Punishment